PENINGKATAN AKTIVITAS BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS IV - Vachry Dhani; Yeni Erita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Improved Learning Activities using ModelsProblem Based Learning (PBL) in Pancasila Education Lessons in Class IV SDN 29 Ganting. This study aims to describe the increase in student learning activities by using modelsProblem Based Learning in Pancasila Education in Class IV SDN 29 Ganting. This research is a classroom action research with qualitative and quantitative approaches. The subjects of this study were 23 class IV students at SDN 29 Ganting. The results of writing this article show that the application of the Learning modelProblem Based Learning (PBL) can improve student learning activities are as follows: Increased learning activities with an average value of 75%, 85.7%, and 92.8%. Thus the application of learning modelsProblem Based Learning (PBL) can improve Pancasila Education learning activities in class IV SDN 29 Ganting.